Agroindústria leiteira no município de Ituiutaba - MG: organização/reorganização socioespacial no período de 1960 a 2013 - Souto, Thales Silveira (2016)
The agricultural production and agrobusiness sector are both essential in the historical process and configuration of the socio-spatial transformations in the city of Ituiutaba - MG. In relation to agriculture, this territorial unit has as base the sugar cane crop, soybean, corn and sorghum, which represent 98.38% of the total area (ha) under cultivation of temporary crops (IBGE, 2013). Regarding to livestock, it highlights the beef cattle and milk, that represent 57.38% of the workforce of the herds (IBGE, 2013). But in the agrobusiness sector, the main units are the sugarcane mill British Petroleum - BP and dairy products: The Fazendeira, dated 1938, Nestlé, deployed in 1974 and the Canto de Minas who started milk processing in 1994. Emphasizing the importance of the dairy agrobusiness in this city, it highlights the growth of the milk quantity produced that was 475,8% between 1974 to 2013 (IBGE, 2013). The Nestlé installation in Ituiutaba was essential to the productive and economic reorganization, because whilst there was milk demand the owners of agricultural establishments, who performed other activities, started to produce milk. Thus, the research problem is to analyze the relevance of milk production chain in the socio-spatial organization/reorganization in Ituiutaba city from 1960 to 2013. In this sense, was justified the choice of the territorial unit for research due to its importance in the production of this raw material in local and regional level as well, related to those of either domestic or international source of capital milk processors installed in the city. The rationale of this study focuses in order to understand the dynamics resulting from the development of the dairy production sector and also know the stages of development or stagnation, facing the new dynamics imposed by capital, checking the prospects and obstacles for milk producers. The overall objective is to analyze the socio-spatial dynamics from the implementation of the milk processing agribusinesses in the organization/reorganization of the territorial unit, in the time scale ranging from 1960 to 2013. The specific objectives sought: (a) verify the importance of processing plants for milk implementation in the city of Ituiutaba for maintenance and/or growth of the productive sector; (b) analyze the socio-spatial transformation caused by this territorial unit, through the dairy agribusiness implementation and (c) know the reality experienced by the dairy producer from Ituiutaba.The development of this research was structured in methodological steps. At first, there was the theoretical survey, seeking the scientific basis for understand the aspects related to the importance of the agricultural sector in the Brazilian socio-spatial transformation, highlighting the Cerrado, connecting to the reality displayed in Ituiutaba; in the second stage was based in the collection of data in the Census of Agriculture IBGE, for the years 1960, 1970, 1980, 1996, and 2006, was collected data in the Pesquisa Pecuária Municipal (1974 to 2013) available in SIDRA/IBGE (IBGE System of Automatic Recovery / Brazilian Institute of Geography and Statistics); later was done the third step, which was consolidated by field work, that was composed with structured interviews to milk producers, to the milk agribusiness, to agencies and development institutions of the agricultural sector as well, to agricultural companies in the Ituiutaba city; the fourth stage led the analysis and subsequent production of charts and tables for better visualization of relevant features to productive agricultural and agribusiness dynamics. Therefore, was diagnosed the importance that the dairy production sector has to the Ituiutaba city, as also it was made possible by the dynamic agricultural and agro-industrial sector in both rural transformation process and the Urban territorial unit study lab.